Citrus Huanglongbing correlated with incidence of Diaphorina citri carrying Candidatus Liberibacter asiaticus and citrus phyllosphere microbiome - Hu, Yang; Meng, Youqing; Yao, Liangjin; Wang, Enguo; Tang, Tao; Wang, Yunsheng; Dai, Liangying; Zhao, Mingping; Zhang, Hong-en; Fan, Xiaoyan; Luo, Luyun; Xiang, Wei; et al. (Frontiers in Plant Science, 2022)
In China, citrus Huanglongbing (HLB) disease is caused by the Candidatus Liberibacter asiaticus bacterium, which is carried by the Asian citrus psyllid Diaphorina citri Kuwayama. It was hypothisesed that the epidemic of the HLB may related with the rate of bacterium presence in the insect vector and bacterium content in plant tissues, as well as the phyllosphere microbe communities changes. This study systematically analyzed the presence or absence of Ca. L. asiaticus in citrus tree leaves and in the insect vector D. citri over a 6-year period using real-time PCR. Inaddition, changes in the number of bacteria carried by D. citri over 12 months were quantified, as well as the relationship between the proportion of D. citri carrying Ca. L. asiaticus and the proportion of plants infected with Ca. L. asiaticus were analyzed. Reults showed that the proportion of D. citri carrying bacteria was stable and relatively low from January to September. The bacteria in citrus leaves relatively low in spring and summer, then peaked in December. The proportion of D. citri carrying bacteria gradually declined from 2014 to 2019. The proportion of D. citri carrying Ca. L. asiaticus showed a significant positive correlation with the proportion of diseased citrus. The phyllosphere bacterial and fungal communities on the healthy citrus leaf were significantly different with the disease leaf in April and December. Pathogenic invasions change the citrus phyllosphere microbial community structure. It could be summuriezed that citrus Huanglongbing correlated with incidence of Diaphorina citri carrying Candidatus Liberibacter asiaticus and citrus phyllosphere microbiome.